2011
DOI: 10.1016/j.parkreldis.2011.07.008
|View full text |Cite
|
Sign up to set email alerts
|

The relation between depression and parkin genotype: The CORE-PD study

Abstract: Background Mutations in parkin are a known genetic risk factor for early-onset Parkinson’s disease (EOPD) but their role in non-motor manifestations is not well established. Genetic factors for depression are similarly not well characterized. We investigate the role of parkin mutations in depression among those with EOPD and their relatives. Methods We collected psychiatric information using the Patient Health Questionnaire and Beck Depression Inventory II on 328 genotyped individuals including 88 probands w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…Two studies showed an association between LRRK G2019S mutations and higher depression scores [47, 48]. In a separate study of early onset PD patients, unaffected relatives of probands with compound heterozygous PARK2 mutations were more likely to have higher depression symptom scores [49], as compared with relatives of probands without PARK2 mutations. Two earlier studies suggested a relationship between depressive symptoms in PD and serotonin transporter gene polymorphisms [50, 51].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Two studies showed an association between LRRK G2019S mutations and higher depression scores [47, 48]. In a separate study of early onset PD patients, unaffected relatives of probands with compound heterozygous PARK2 mutations were more likely to have higher depression symptom scores [49], as compared with relatives of probands without PARK2 mutations. Two earlier studies suggested a relationship between depressive symptoms in PD and serotonin transporter gene polymorphisms [50, 51].…”
Section: Pathophysiologymentioning
confidence: 99%
“…In a recent article studying depression in Parkin mutation carriers with and without PD, an increased risk of depression was observed in compound‐heterozygous nonmanifesting carriers (NMC), who were all relatives of early‐onset manifesting carriers (MMC). However, a clear association between risk of depression and genotype could not be shown 7…”
mentioning
confidence: 93%
“…However, a clear association between risk of depression and genotype could not be shown. 7 In this study, we aimed to characterize depression, anxiety, and their effect on QoL in monogenic PD compared to patients with IPD, healthy controls, and disease controls with treated depression.…”
mentioning
confidence: 99%
“…Higher scores indicate more symptoms. BDI‐II scores for 88 of 104 probands and 218 of 257 relatives were previously reported …”
Section: Methodsmentioning
confidence: 99%
“…Few studies have systematically investigated the association between PARKIN genotype and psychiatric co‐morbidities of PD . We previously found no association between mutation status and depression among PD patients, but showed that asymptomatic carriers of two mutations had higher rates of depression than asymptomatic noncarriers, adding further support to evidence that depression is a prodromal symptom . Obsessive‐compulsive (OC) symptoms have been hypothetically linked to PD because both conditions involve the frontostriatal circuits .…”
mentioning
confidence: 87%